2013
DOI: 10.1111/ijd.12250
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and safety of cetirizine versus rupatadine in chronic spontaneous urticaria: a randomized, double‐blind, 6‐week trial

Abstract: Background Urticaria is a distressing condition associated with diverse clinical presentations. Chronic spontaneous urticaria (CsU) is characterized by wheals and angioedema. Its treatment requires an algorithmic approach to identify the optimum medication. Objectives Cetirizine is commonly used in the treatment of urticaria. Rupatadine is a selective non‐sedating H1‐antihistamine approved for the treatment of CsU. This trial was conducted to ascertain whether the properties of rupatadine offer advantages over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…One study, Anuradha et al stopped systemic corticosteroids for 4 weeks and the mean eosinophil % was 4.2% (n = 60), while the median was 364 10 6 /L [ 23 ]. Another study, Dakhale et al, stopped systemic corticosteroids for 8 weeks and the mean eosinophil % was 6.8% (n = 64) [ 24 ]. The absolute eosinophil count was not provided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study, Anuradha et al stopped systemic corticosteroids for 4 weeks and the mean eosinophil % was 4.2% (n = 60), while the median was 364 10 6 /L [ 23 ]. Another study, Dakhale et al, stopped systemic corticosteroids for 8 weeks and the mean eosinophil % was 6.8% (n = 64) [ 24 ]. The absolute eosinophil count was not provided.…”
Section: Resultsmentioning
confidence: 99%
“…Where corticosteroids weren’t held, the mean eosinophil percentage, mean absolute eosinophil count and median absolute eosinophil count were not elevated. Studies did find that antihistamines reduced peripheral blood eosinophil counts in CSU subjects which may help explain these findings [ 23 , 24 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rupatadine treatment in the established schemes is suitable to reduce the burden of recurrent CSU episodes in those patients. In previous studies, it was shown that rupatadine was even more effective than desloratadine, cetirizine and levocetirizine with regard to both, benefits in clinical outcome and patients’ QoL [ 28 – 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rupatadine, a dual second-generation H1 antihistamine and PAFR blocker has proven clinically efficacious in urticaria, allergic rhinitis, and rhinoconjunctivitis [17, 27]. Randomized trials comparing rupatadine and levocetirizine demonstrate that rupatadine is better tolerated and more effective for chronic urticaria (Table 1) [41, 42]. Rupatadine currently is not available in the USA.…”
Section: Platelet-activating Factormentioning
confidence: 99%